Ambiente criativo: estudo de caso na cidade de Natal/RN - Cruz, Fernando Manuel Rocha da (2014)
The creative city can be identified by their cultural quarters, the existence of creative territories or the dynamics of a creative class. Whether we classify a city as creative, we can conceive that as creative environment charge of development of creativity in organizational settings, but also in urban dynamics and public participation itself. The creativity social phenomenon is an important and essential element but it is not the only contributor to the development of the creative environment. From the city of Natal, state of Rio Grande do Norte, we tried to identify and characterize statistically the main creative sectors. Thus, we set off for the application of semi-structured interviews in the three key creative sectors: Research, Architecture and Advertising. Besides, the proposal of a summary table of the analysis of the creative industries in the city of Natal, the research allowed to propose an analysis model of urban environment of a city whose main dimensions are population, cultural resources, networks and public policy